Carl Jung's Shadow and Persona: The Process of Individuation in Gone Girl by Gillian Flynn (2012) - Mizat,Hadjer; Mahboub, Maria; Naoumi,Mohamed (University of Ammar Theledji -Laghouat, 2021)
The psyche of characters within literary works has become one of the essential elements for analysis because it contributes to the values of the story. Since the persona and the shadow archetypes are constantly recurrent in Gone Girl novel by Gillian Flynn, we will use Jung’s theory of the archetypes to examine the individuation process in the main characters. Considering that the analysis focuses on characters’ personalities, we will use the psychoanalytical approach to conduct this study through the descriptive, analytical, qualitative research method. We will use the novel as a primary source alongside documents, papers and related works to collect data. The first chapter provides the theoretical background of psychology and its impact on personal and social life. It also discusses the influence of Freud’s psychoanalytic theory on literary works. The second chapter represents the theoretical framework upon which the analysis will take place. It focuses on the Jungian theory of archetypes, persona and shadow, and their effect on individuation. Finally, the third chapter gives a summary of Gillian’s Gone Girl novel plot. In addition to the analysis of Amy and Nick characters to examine individuation. The objectives of this study are first to explore the role of psychology in comprehending human behaviours. The second one is to highlight the influences of Carl Jung’s psychoanalysis on literature. Lastly, to investigate the way the novel portrayed individuation in the main characters. There are two points to conclude based on the findings and discussion. First, Amy failed to achieve self-realisation because her shadow is more dominant than her persona. Second, Nick did not completely fail, but he is working towards individuation